From agronomy to molecular genetics and proteomics in an effort to improve nitrogen use efficiency in crops - Chandna, Ruby; Hakeem, Khalid Rehman (Springer, 2013)
Agriculture plays significant role in the sustaining human society among most of the developing countries. The agricultural practices are dependent on the application of the nitrogenous fertilizers. The excessive application of nitrogenous fertilizer contributes enormously to the environmental pollution. So, in today’s scenario there is growing need to reduce N fertilizer applications thereby improving plant’s N-use efficiency (NUE). Initially, various studies have been carried out to improve inputs of N fertilizers interaction with soil, water and air but low efficiency of the plant to make use of available N has initiated biological interferences. In this article, we will be discussing the possible technologies applied towards understanding the genetic control of nitrogen use efficiency and its improvement in crops. The classification/identification of suitable target candidates like phenotypes, genotypes or molecular markers, for the upgrading of NUE poses big confront. Therefore, it is necessary to understand NUE and its importance with respect to economy and environment. Also, to figure out the diverse approaches for progress towards NUE enhancement and possibilities for future development.